Suffering saints: Jansenists and Convulsionnaires in France, 1640 - 1799 - Strayer, Brian Eugene (Sussex Academic Press, 2008)
Introduction: Jansenism in France -- Who were the Jansenists? -- What was Jansenism? -- Sunrise over Port-Royal, 1600-1661 -- Sunset over Port-Royal, 1661-1711 -- Jansenism enters the political arena, 1713-1750 -- Jansenism loses its raison d'être, 1751-1799 -- The shaking of Jansenism: miracle cures and the convulsionnaires, 1727-1740 -- Crucifying Jansenism: Grands Secours and the death of convulsionism, 1741-1799 -- Jansenism and convulsionism, 1650-2000: an historiographic essay -- Conclusion: the impact of Jansenism in France